PROFIL LIPID PADA LANJUT USIA SEBAGAI FAKTOR RESIKO PENYAKIT METABOLIK DI KENDARI SULAWESI TENGGARA - Ani Umar; Firdayanti Firdayanti; Angriani Fusvita (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Metabolic diseases are a global health problem that is increasing especially in developed countries (Silva et al., 2020). The incidence is higher in the elderly population due to physiological and metabolic changes associated with aging (Silva et al., 2020). Lipid profile is an important indicator in assessing the risk of metabolic diseases. Blood lipids include total cholesterol, LDL (Low Density Lipoprotein), HDL (high Density Lipoprotein), and triglycerides, playing a major role in the development of cardiovascular disease. (Emmanuel et al., 2022) The purpose of this study was to determine the lipid profile in the elderly as one of the metabolic diseases. This study used a cross-sectional design with a target population of 50 elderly individuals aged 60 years and over. data were collected through direct measurement of lipid profiles including total cholesterol, triglycerides, HDL, and LDL using the CHOD-PAP method (Chlorimetric Derivate- Para Amino Phenazone) using a spectrophotometer. The results of the study showed that from 50 elderly patients, the lipid profile levels obtained were total cholesterol levels in the normal category with an average cost of 1.66, where 66% of respondents obtained normal cholesterol levels, while 34% showed high cholesterol levels. in the triglyceride variable, the results obtained were 72% of respondents had normal triglyceride levels, while 28% experienced an increase. HDL levels showed more positive results, with 82% of respondents having good HDL levels, and only 18% having low HDL levels, and, analysis of LDL levels revealed that only 8% of respondents had high LDL levels, while 92% had normal LDL levels in men and women, TG/HDL limits are <150 and> 40 mg/dl, and cholesterol limits <200 and LDL <150.